Innovative Enjoyable Learning Media for Enhancing Students' Literacy in Excretory System Disorders - Arifianti, Aprillia; Mulyati, Yayuk; Danissa, Fanny; Hasan, Said; Wicaksono, Azizul (Indonesian Journal of Biology Education, 2024)
Students' scientific literacy skills are currently relatively low, one of the influencing factors is the lack of use of learning media that can train students' scientific literacy skills. This research aims to develop ELGASE (Enjoyable Learning Gangguan Sistem Ekskresi) media that is valid and practical. The media developed is not only to train students' scientific literacy skills, but also as an effort to make learning strategies more enjoyable for students. The method used in this research is RnD (Research and Development) with the ADDIE model including needs analysis, design, development, implementation and evaluation. At the implementation stage, this research stopped at the teacher and student practicality tests. The results indicate that the ELGASE learning media is both valid and practical, receiving high scores from 2 expert evaluations and positive feedback from students and teachers. The media validation results have a very valid category, namely 91.4% for media validation and 92.5% for material validation. The results of the practicality test by teachers and students obtained presentations of 82.4% and 92% respectively in the very practical category. In conclusion, the developed ELGASE learning media is valid and practical for use in educational settings, providing a valuable tool for improving science literacy and making learning more enjoyable for students.